Effects of Building a Levee on the Vernacular Landscape along the Mekong River: A Case Study of Tha Uthen Community, Tha Uthen District, Nakhon Phanom Province - Wapeesilp, Kowit; Mekkapan-opas, Songbhop; Martmuang, Supachoke (Journal of Landscape Architecture and Planning, 2023)
The objectives of this research were to 1) study the elements of the vernacular landscape along the Mekong River, Tha Uthen Community, and 2) study the effects of building a levee on the Mekong River on the vernacular landscape along the Mekong River, Tha Uthen Community. Research tools werean in-depth (unstructured) in terview, participant observation, and focus group. The research found that the Tha Uthen community had five elements of the vernacular landscape along the Mekong River, including 1) the Mekong River, 2) the riverbanks of the Mekong River, 3) trees, 4) buildings and structures along the riverbanks of the Mekong River 5) humans. There were four effects of building a levee on the vernacular landscape along the Mekong River, including 1) loss of agricultural land along the Mekong River, which was the important vernacular landscape along the Mekong River; 2) food security in communities was reduced; especially agricultural products; 3) traditional way of life of communities related to the Mekong River had changed; 4) elements of the vernacular landscape along the Mekong River were destroyed and might loss in the near future.